2001
DOI: 10.1093/carcin/22.8.1213
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of retinoic acid concentration supresses ethanol-enhanced c-Jun expression and hepatocyte proliferation in rat liver

Abstract: Chronic and excessive ethanol intake decreases hepatic retinoic acid (RA) concentrations, which may play a critical role in ethanol-induced hyperproliferation in hepatocytes. The present study was conducted to determine whether RA supplementation in chronic ethanol-fed rats could restore hepatic RA concentrations to normal levels and modulate hepatocyte hyperproliferation. Male Sprague-Dawley rats were divided into four groups: control, ethanol-fed, ethanol-fed + 50 microg all-trans-RA/kg body wt and ethanol-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
90
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 38 publications
9
90
1
1
Order By: Relevance
“…This explains parenchymal hyperproliferation, as AP-1 is a central complex downstream of various growth factors, oncogenes and tumor promoters (Chiu et al, 1988). Most interestingly, supplementation of animals with all-trans-RA to normal RA levels not only led to a decrease in AP-1 (c-jun and c-fos) gene expression, but also to normalization of hepatic proliferation, as expressed by proliferating cell nuclear antigen expression (Chung et al, 2001). In summary, these data suggest that low hepatic RA levels due to chronic alcohol misuse may favor proliferation and malignant transformation of hepatocytes via upregulation of AP-1 (c-jun and c-fos) gene expression.…”
Section: Interaction With Retinoidsmentioning
confidence: 97%
See 1 more Smart Citation
“…This explains parenchymal hyperproliferation, as AP-1 is a central complex downstream of various growth factors, oncogenes and tumor promoters (Chiu et al, 1988). Most interestingly, supplementation of animals with all-trans-RA to normal RA levels not only led to a decrease in AP-1 (c-jun and c-fos) gene expression, but also to normalization of hepatic proliferation, as expressed by proliferating cell nuclear antigen expression (Chung et al, 2001). In summary, these data suggest that low hepatic RA levels due to chronic alcohol misuse may favor proliferation and malignant transformation of hepatocytes via upregulation of AP-1 (c-jun and c-fos) gene expression.…”
Section: Interaction With Retinoidsmentioning
confidence: 97%
“…Accordingly, RA levels in the liver of ethanol-fed rats were significantly decreased compared with control pairs fed an isocaloric control diet containing equal amounts of vitamin A ). It has recently been shown that ethanol causes an additional local deficiency of RA in the liver, resulting from enhanced RA catabolism due to induction of CYP2E1 (Chung et al, 2001). In the same study, treatment of ethanol-fed rats with chlormethiazole, a specific CYP2E1 inhibitor, restored both hepatic and plasma RA concentrations to normal levels.…”
Section: Interaction With Retinoidsmentioning
confidence: 99%
“…As already mentioned, chronic alcohol consumption induces the activity of hepatic cytochrome P450 enzymes (Lieber, 1994b), and these enzymes, predominantly CYP2E1, are involved in ROL and RA metabolism. In a recent study by Liu et al (2002) treatment of rats with high-doses of ethanol led to a reduction in hepatic ROL and retinyl ester concentrations and the occurrence of several polar retinoid metabolites, when compared with rats pair-fed with an isoenergic control diet containing the same amount of vitamin A. Chlormethiazole, an efficient inhibitor of CYP2E1, can prevent this ethanol-enhanced metabolism of ROL and RA in rats (Liu et al 2001(Liu et al , 2002. Chlormethiazole also reduces the formation of oxidative polar metabolites of ROL (Liu et al 2002).…”
Section: Retinoidsmentioning
confidence: 99%
“…It has been shown that hepatocytes become hyperproliferative after chronic ethanol treatment (Halsted et al 1996;Chung et al 2001Chung et al , 2002, which may contribute to ethanolinduced disease. Recent studies have demonstrated that the restoration of ethanol-lowered RA levels to normal levels alters hepatocyte proliferation and apoptosis in alcohol-fed rats (Chung et al 2001(Chung et al , 2002, indicating that retinoids could protect against alcohol-induced diseases.…”
Section: Retinoidsmentioning
confidence: 99%
See 1 more Smart Citation